PENGARUH SIKAP, NORMA SUBJEKTIF, KENDALI PERILAKU DAN RELIGIUSITAS TERHADAP INTENSI MENGGUNAKAN UANG ELEKTRONIK - ferinaldy ferinaldy; Muslikh Muslikh; Nurul Huda (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2019)
Abstract: The purpose of this study is to examine the factors of attitude, subjective norms, behavioral control, and religiosity towards behavior through the intention to use electronic money in YARSI University students. Based on a literature review, this research hypothesis states that attitudes, subjective norms, behavioral control, and religiosity affect behavior through intention. This study uses survey data from questionnaires to 127 respondents. Hypothesis testing techniques are done by using SEM analysis with Lisrel software. The results of data processing indicate that the Attitude Variable, Subjective Norms, Behavioral Control, and Religiosity have a significant influence on behavior through the intention to use electronic money. Intention variable has a significant effect on behavior using electronic money with a t-value of 7.86. Behavioral Control Variables and subjective norms have a greater influence on behavior through the intention to use electronic money than other variables. Suggestions based on research results: first, it is necessary to expand information to the public about the benefits of using electronic money. Second, it is necessary to increase the number of merchants or expand the place of use so that the use of electronic money becomes more extensive and maximal. Keywords: intention, electronic money, TPB, SEM.